ON THE WAY TO AN EFFECTIVE MECHANISM OF TAX ADMINISTRATION IN THE CONDITIONS OF DIGITALIZATION - Abdusherozov Abdullo Baxtiyorovich (American Journals, 2025)
In the article, at the current stage of the liberalization of the economy and the modernization of the tax system in the Republic of Uzbekistan, the advantages and unique features of the creative approach to effective measures to regulate and stimulate economic development through taxes are scientifically justified.
Keywords: Tax system, taxes, taxation, tax administration, tax regulation, taxpayer.